Gender-Based Regional Planning in Poverty Alleviation in the Strategic Area of Subosukawonosraten, Central Java - Marina Ramdhani Ciptaningtyas; Bhimo Rizky Samudro; Sarjiyanto; Arif Rahman Hakim (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to examine the effects of women’s parliamentary representation, the Gender Development Index (GDI), regional gross domestic product (GDP) per capita, and female labor force participation on poverty reduction in the Subosukawonosraten strategic region of Central Java. The study hypothesizes that all independent variables negatively influence poverty. The research employs a quantitative approach using panel data from seven districts/cities over the period 2012–2024. A Random Effect Model (REM) regression is applied after conducting model selection tests, including the Breusch–Pagan LM, Chow, and Hausman tests. The data are obtained from official statistical publications, and variables include poverty rate, women’s representation, GDI, GDP per capita, and female labor participation. The results indicate that women’s parliamentary representation (coefficient = −1.047; p = 0.001) and GDP per capita (coefficient = −1.312; p = 0.000) have a significant negative effect on poverty, confirming their critical role in poverty alleviation. In contrast, GDI and female labor force participation show no statistically significant direct effects, suggesting their influence may be indirect or mediated by other factors. These findings imply that strengthening women’s political participation and promoting regional economic growth are effective strategies for reducing poverty. Policymakers should integrate gender-inclusive governance with economic development programs. Future research is recommended to incorporate mediating variables and mixed-method approaches to better capture the complex dynamics of gender and poverty.